DEPRESSION FOUND IN GREEN DAY’S SELECTED SONGS: “BASKET CASE” AND “BOULEVARD OF BROKEN DREAMS” (PSYCHOLOGICAL APPROACH) - Bata, Levi M; Wanggai, Febe F I; Doi, Maksimilianus (Lantern: Journal of Language and Literature, 2024)
This study discusses Depression in the lyrics of the Green Day song. The focus is on the depressive symptoms implied in the lyrics of the songs "Basket Case", and "Boulevard of Broken Dreams". The purpose of this research is to find out the types of depression, the causes of depression, and the effects of depression in the lyrics of Green Day's songs entitled "Basket Case", and "Boulevard of Broken Dreams" and to describe the symptoms of depression described in the lyrics of the two songs. . This study uses a qualitative descriptive approach and data analysis collection techniques include collecting data, finding words and sentences and including words and sentences that reflect the type of depression. The results of this study found that the symptoms of depression that appear in the lyrics of the songs "Basket Case" and "boulevard of broken rage" include low self-evaluation, loss of emotional attachment, and negative feelings about self.